2018
DOI: 10.1155/2018/2459696
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Amblyopia Treatment with Glasses Only and Combination of Glasses and Open-Type Binocular “Occlu-Pad” Device

Abstract: We evaluated amblyopia treatment, comparing training with glasses only and training with glasses and the Occlu-pad, a binocular open-type amblyopia training device. Forty-six children (4.8 ± 1.1 years) diagnosed with anisometropic amblyopia, all wearing complete correction glasses, were treated either with glasses only, or with glasses in combination with the Occlu-pad (training time: 2 days a week, 30 minutes per day). We compared visual acuity scores at 3 and 6 months after treatment had started, and examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 15 publications
0
24
1
Order By: Relevance
“…For instance, Singh et al reported significant differences in their RCT, since the group that received dichoptic therapy and patching improved 2.4 lines in VA, while the patching group enhanced 1.8 lines [23]. In addition, good treatment compliance (mean of 69% or more) with visual therapy was reported by many authors [24][25][26][27][28], except a rate of 50% of compliance reported by Birch et al [21]. is is an important advantage compared to patching, as its compliance ranges from 44% to 57% [31].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…For instance, Singh et al reported significant differences in their RCT, since the group that received dichoptic therapy and patching improved 2.4 lines in VA, while the patching group enhanced 1.8 lines [23]. In addition, good treatment compliance (mean of 69% or more) with visual therapy was reported by many authors [24][25][26][27][28], except a rate of 50% of compliance reported by Birch et al [21]. is is an important advantage compared to patching, as its compliance ranges from 44% to 57% [31].…”
Section: Discussionmentioning
confidence: 98%
“…According to the results of this systematic review, three main aspects should be analyzed in studies evaluating the effect of active vision therapy in amblyopia due to its importance in daily practice: visual acuity improvement, dose-response ratio, and adherence to treatment. Active visual therapy with dichoptic therapy, perceptual learning, anaglyph glasses, or some specific video games is effective in the treatment of anisometropic amblyopia to improve visual acuity [21][22][23][24][25][26][27][28] when it is compared with only glasses [24,26], patching [23,28], or placebo [21]. According to some authors, this improvement seems to be similar to patching [24,26,27], without a clear evidence confirming that vision therapy is more or less effective than patching for the treatment of anisometropic amblyopia in children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the fact that they seem to be effective, they also have some features which could be a limitation. Some of these treatments are based on dichoptic training or monocular stimulation, and use eye–hand coordination games [ 12 , 14 , 46 ] and popular films [ 47 ] which are not specifically designed for treating amblyopia, or do not adjust the difficulty of the training to the patient’s progress. However, there are four types of stimuli which have shown to be effective in clinical research that can be easily added to the amblyopia training software, with the possibility of modification according to the patient’s evolution, and these are letter optotypes [ 48 , 49 ], Gabor’s patches [ 9 , 48 , 49 , 50 , 51 , 52 ], Vernier’s stimuli [ 53 ] and random-dot stereograms [ 16 , 54 ] ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Over the last few years, vision therapy has been suggested to be an effective option to promote visual rehabilitation and even to accelerate recovery when combined with patching [ 8 ]. New trends in computer-based active vision therapy have been developed for amblyopia treatment, such as the use of perceptual learning environments [ 9 , 10 , 11 ], dichoptic stimulation [ 12 , 13 , 14 ] and binocular training [ 15 , 16 ]. These video games use visual and perceptual tasks, such as orientation discrimination or letter recognition, among others, to cause a response in neuro-modulatory pathways and the enhancement of attentional skills, according to neurophysiological studies [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%